2017
DOI: 10.1039/c7nr02530k
|View full text |Cite
|
Sign up to set email alerts
|

A facile strategy for fine-tuning the stability and drug release of stimuli-responsive cross-linked micellar nanoparticles towards precision drug delivery

Abstract: Precision drug delivery has great impact on the application of precision oncology for better patient care. Here we report a facile strategy for fine-tuning the stability, drug release and responsiveness of stimuli-responsive cross-linked nanoparticles towards precision drug delivery. A series of micellar nanoparticles with different levels of intramicellar disulfide crosslinkages could be conveniently produced with a mixed micelle approach. These micellar nanoparticles were all within a size range of 25–40 nm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Additionally, broad size distribution occurred due to casein reassembled nature but as the figure ( Figure 7 A) shows more than 90% of micelle intensity lies in the 200 nm particle size range, indicating the suitable particle size of our micelle. As long as the particles remain within the size range suitable for systemic administration and able to escape the leaky tumor vessels to reach the tumor, and prevent renal clearance and uptake by reticuloendothelial system, they could be used as smart nanocarriers, previously many studies in our lab [ 41 , 49 , 50 ] and also some other studies [ 51 , 52 , 53 ] supported that particles even though heterogeneous in size could be a fantastic nanocarrier system for efficient and tumor-targeted delivery of anti-cancer drugs and genetic materials.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, broad size distribution occurred due to casein reassembled nature but as the figure ( Figure 7 A) shows more than 90% of micelle intensity lies in the 200 nm particle size range, indicating the suitable particle size of our micelle. As long as the particles remain within the size range suitable for systemic administration and able to escape the leaky tumor vessels to reach the tumor, and prevent renal clearance and uptake by reticuloendothelial system, they could be used as smart nanocarriers, previously many studies in our lab [ 41 , 49 , 50 ] and also some other studies [ 51 , 52 , 53 ] supported that particles even though heterogeneous in size could be a fantastic nanocarrier system for efficient and tumor-targeted delivery of anti-cancer drugs and genetic materials.…”
Section: Resultsmentioning
confidence: 99%
“…Stability is one of the significant factors for therapeutic effects, and the encapsulation efficiency is considered as the key criterion to evaluate colloidal stability 34. In this study, the BV/PTX@Au@PDA/DOX was stored at 4 for a period of 0, 5, 10, and 15 days.…”
Section: Resultsmentioning
confidence: 99%
“…By mixing telodendrimers with and without cysteine moieties, they investigated the optimal level of cross-linking in relation to micelle properties, such as stability, drug release, and responsiveness to the reductive environment. It was reported that cross-linking levels of 20% and 50% were more effective antitumor formulations against in vivo SKOV-3 ovarian cancer cells [ 185 ].…”
Section: Telodendrimersmentioning
confidence: 99%